Resection of hepatocellular cancer ≤2 cm: Results from two Western centers1. Issue 4 (25th January 2013) - Roayaie, Sasan; Obeidat, Khaled; Sposito, Carlo; Mariani, Luigi; Bhoori, Sherrie; Pellegrinelli, Alessandro; Labow, Daniel; Llovet, Josep M.; Schwartz, Myron; Mazzaferro, Vincenzo
Abstract Asian series have shown a 5‐year survival rate of ≈70% after resection of hepatocellular carcinoma (HCC) ≤2 cm. Western outcomes with resection have not been as good. In addition, ablation of HCC ≤2 cm has been shown to achieve competitive results, leaving the role of resection in these patients unclear. Records of patients undergoing resection at two Western centers between January 1990 and December 2009 were reviewed. Patients with a single HCC ≤2 cm on pathologic analysis were included. Thirty clinical variables including demographics, liver function, tumor characteristics, nature of the surgery, and the surrounding liver were examined. An exploratory statistical analysis was conducted to determine variables associated with recurrence and survival. The study included 132 patients with a median follow‐up of 37.5 months. There was one (<1%) 90‐day mortality. There were 32 deaths with a median survival of 74.5 months and a 5‐year survival rate of 70% (63% in patients with cirrhosis). The median time to recurrence was 31.6 months and the 5‐year recurrence rate was 68%. Presence of satellites (hazard ratio [HR], 2.46; P = 0.031) and platelet count <150, 000/μL (HR, 2.37; P = 0.026) were independently associated with survival. Presence of satellites (HR, 2.79; P = 0.003), cirrhosis (HR, 2.3; P = 0.010), and nonanatomic resection (HR, 1.79; P = 0.031) were independently associated with recurrence. Patients with a single HCC ≤2 cm and platelet count ≥150, 000/μL achieved a median survival of 138 months and a 5‐year survival rate of 81%, respectively. Conclusion: Resection of HCC ≤2 cm is safe and achieves excellent results in Western centers. Recurrence continues to be a significant problem. Presence of satellites, platelet count, anatomic resection, and cirrhosis are associated with outcomes after resection, even among such early tumors. Resection should continue to be considered a primary treatment modality in patients with small HCC and well‐preserved liver function. (HEPATOLOGY 2013)